Subtitusion Of Tuna Fish Innards Flour In Biscuit to Improve Nutrition - Nanda Irma ADP; Nadimin Nadimin; Thresia Dewi (Jurusan Gizi Poltekkes Kemenkes Makassar, 2018)
ABSTRACTNutritional problem in Indonesia is still a serious health problem especially malnutrition and stunting. One of the efforts to improve the pattern of food consumption that aims to overcome malnutrition among people, especially proteins and vitamins and minerals is by utilizing tuna fish innards into fish meal innards in the form of biscuits.This study aims to determine the levels of nutrients protein, fat, calcium, iron, and zinc of biscuit with substitution of flour tuna fish innards. The research type is quasi experimental with one only design group design. The results of this analysis were obtained from research conducted by kjedahl method for protein, sochxlet for fat and Spektrofotometri for calcium, iron, and zinc.The results showed that the content of tuna innard biscuit protein was higher by 7.913% compared to biscuits without substitution, the fat content of tuna innard biscuit was higher by 25.18% than the biscuit without substitution, the calcium biscuit level of 61.871%, fe 0%, and the zinc content of the tuna innard biscuit is higher by 7,532% compared to biscuit without substitution.Biscuit with tuna innard substitution can be recommended as complementary foods with various processing improvements. It is suggested to find a way to remove bitter taste on the tuna innard flour.